A sustainable development concept in the light of the Kingdom of God - Matijević, Dalia (Array, 2020)
In searching for answers about the actual relation between two apparently incompatible concepts: the Kingdom of God and the Sustainable Development (SD), we will try to put them side by side and use respective comparative findings, in order to see if they can work together and possibly benefit from each other. The aim is to better understand future perspectives that are opening for the church within the contemporary context. The two concepts considered in this research, the Kingdom of God and SD, are never supposed to be separated. Although coming from different sources, using different languages, and springing out from different socio-political contexts, they tackle the same set of universal issues; both are eagerly anticipated, their fulfilment is of utmost importance, they both call for profound personal and communal transformation, both are powerfully creative and innovative, and both have the capacity to mobilize communities, peoples, and resources. The intersections between the SD and the Kingdom of God create opportunities for the church to practice shalom and to nurture hesed in the world by encouraging inclusiveness, lobbing for social justice, carrying for the poor and marginalized, and extending love and compassion onto the whole of creation, without losing its genuine identity. Within the SD framework, the role of the church is to make sure that nobody is left behind. The church might be the best part of the SD practice by persistently insisting on the same universal set of Kingdom values no matter how circumstances are changing.